ROLE OF RELATIVE CODON USAGE (RSCU) ON INFECTIVITY AND VIRULENCE OF FOWL ADENOVIRUS ISOLATED FROM INFECTED IRAQI POULTRY - Abdulla, Aya .R.; Jabbar, Rebah .N.; Allawe, Aida .B. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate the role of codon usage on infectivity and virulence of fowl adenovirus. The PCR amplicon sequence revealed that loop1 has a hypervariable region and is adjacent to loop2 on Hexon A segment, while Hexon B segment has a less variable region. The fiber gene is similar among isolates, with differences associated with the virus. Most belong to fowl adenovirus-4, with others in type 8b and E. The study revealed increased effective nucleotide codons in isolates 5, 33, 44, and 15 in Fiber gene, Loop2, and Loop1genes. The study analyzed the impact of mutation on codon usage, hypervariable regions 1-4, and the effective number of codons by determining high and low effective usage. Fowl adenovirus has hypervariable regions that extend at a specific area along HexA segment. The study found stable regions in viruses with variable nucleotides, indicating their evolutionary capability and abundance of amino acids Alanine, Glycine, Proline, Arginine, and Serine, as detected by relative codon usage calculation. The high usage of these codons may result in mutational pressure, potentially aiding in understanding the infectivity and pathogenicity of Fowl adenoviruses through natural selection.